Mechanical, tribological and cytocompatibility properties of cellulose nanofiber-reinforced ultra-high molecular weight polyethylene composites - Sharip, Nur Sharmila (2022)
Ultra-high molecular weight polyethylene (UHMWPE) tibial insert in knee prosthesis possesses limited longevity due to the continuous sliding and rolling movement of the highly stiff metal femoral counterpart onto its surface which leads to the abrasion and wear. This generates wear debris that subsequently contributes to the inflammation. The use of the appropriate nanofiller in the UHMWPE may improve the polymer stiffness and wear resistance. Hydrophilic cellulose nanofiber (CNF) was selected as the nanofiller in this research. The effects of blending processing conditions and residual lignin in CNF on the characteristics of the UHMWPE/CNF bionanocomposites were evaluated. Optimization of the melt blending processing conditions was conducted by varying the temperature, rotational speed, and mixing time using a central composite design (CCD) of response surface methodology (RSM). The mechanical properties of the UHMWPE/CNF bionanocomposites were greatly influenced by the temperature and mixing time, while the rotational speed moderately affected the Young’s modulus. At the optimum processing conditions (150°C, 60 rpm, and 45 minutes) a homogeneously distributed CNF contributed to the highest values of Young’s Modulus, yield strength, tensile strength, and elongation at 366 MPa, 22.8 MPa, 28.0 MPa, and 462%, accordingly. These values surpassed the standard requirement of fabricated UHMWPE for a joint application. A non-melt blending process through ethanol mixing was then evaluated to elucidate the effect of the blending process on the mechanical properties of the bionanocomposites. The field emission scanning electron microscopy (FE-SEM) analysis revealed a better mechanical interlocking between UHMWPE and CNF from the bionanocomposites sample produced through the melt blending process which resulted in higher yield strength, elongation at break, Young’s modulus, toughness, and crystallinity by 28%, 61%, 47%, 45%, and 11%, respectively, compared to those produced through ethanol mixing (non-melt blending processing). Increasing the CNF content via melt blending processing did not improve the tensile properties of the bionanocomposites due to the weakened hydrophobic interfacial interaction between UHMWPE molecules in the presence of high CNF content. Residual lignin in the CNF was postulated to improve the interaction between UHMWPE and CNF, and hence ligno-cellulose nanofiber (LCNF) with 22.5% lignin was incorporated in to the UHMWPE. It was interesting to note that the tensile strength, toughness, and flexural strength were increased by 21%, 9%, and 51%, respectively, when 0.5 wt.% LCNF was used in the UHMWPE, as compared to 0.5 wt.% CNF. Hydrophobic lignin in LCNF is expected to form a better interaction between UHMWPE and LCNF. The efficiency of CNF and LCNF as fillers for improving the wear resistance was also confirmed through a wear testing analysis using a pin-on-disk tribometer. The enhancement of wear resistance properties by 33% and 42% was achieved for UHMWPE/0.5%CNF and UHMWPE/0.5%LCNF, respectively. This is supported by the reduction in abrasive wear as evidenced through the FE-SEM analysis. Cytocompatibility of UHMWPE/0.5%CNF and UHMWPE/0.5%LCNF on osteoblast-like cells MG-63 was evaluated to further characterize the materials’ suitability for knee prosthesis application. The spindle-like appearance of cells on both bionanocomposites with nearly zero shape factors (0.2 to 0.4) indicated a good cell adherence and attachment. Cell viability and ALP activity of MG-63 were higher and similar to the UHMWPE/0% filler, respectively, indicating the non-toxic effect of CNF and LCNF inclusion in the UHMWPE bionanocomposites. Overall, the incorporation of CNF and LCNF in UHMWPE through melt blending contributed to a better wear resistance, higher Young’s modulus and excellent cytocompatibility against osteoblastic MG-63 cells. These findings indicate the suitability and potential of CNF and LCNF as nanofiller in UHMWPE for the tibial insert application, with the advantages of being renewable, organic and non-toxic.